SWEARWORDS USED BY BENGKULUNESE: A CASE STUDY OF TABOO EXPRESSIONS - Merry Rullyanti (Premise: Journal of English Education and Applied Linguistics, 2014)
Swearwords are natural part of our language. They are used as the most healing way to throw away some extra frustration or anger in a difficult situation. Anderson  lists  three  different  motives  for swearing:  psychological  motives, social motives and linguistic motives.  The primary aim in this research is to find out swearwords that are commonly used by Bengkulunese people and the most frequent motives behind them. There are 20 Bengkulunese people as the participants of this research who filled in questionnaire. The questionnaire contained a table which consisted of two columns. The first is the swearwords column and the second one is the circumstances of the occurred swearwords which must be filled in by the participants completely. Based on the swearwords gained from the participants, there are 43 swearwords that are generally used by them in their daily speaking activity. Some of them are still in Indonesian language version and some other swearwords are from Bengkulunese language version. For example the word “sialan” and “kurang ajar” are Indonesian languages that are still understood by those who are not Bengkulunese, while the word “sea’”, “bigal”, or “cuk mak” are based from Bengkulunese language.